Applications of Transition Metal Catalysis in Drug Discovery and Development. An Industrial Perspective. Edited by Matthew L. Crawley and Barry M. Trost. Issue 21 (19th April 2013) - Medlock, Jonathan; Bonrath, Werner
<x xml:space="preserve">Abstract</x> John Wiley & Sons, Hoboken, 2012. 376 pp., hardcover, € 80.40.—ISBN 978‐0470631324<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>